2012
DOI: 10.1155/2012/723062
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Hypersensitivity Syndrome Reaction Development and Human Herpes Virus-6 Reactivation

Abstract: Background. There are challenges in the clinical diagnosis of drug-induced injury and in obtaining information on the reactivation of human herpes viruses (HHV) during idiosyncratic adverse drug reactions. Objectives. (i) To develop a unified list of drugs incriminated in drug-induced hepatotoxicity and severe cutaneous reactions, in which drug hypersensitivity leads to HHV-6 reactivation and further complication of therapy and recovery and (ii) to supplement the already available data on reporting frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 92 publications
(213 reference statements)
1
28
0
1
Order By: Relevance
“…Among those negative for HHV6, 20 patients were treated with systemic corticosteroids (median total dose 5 mg kg À1 , range 1-16) and five patients were managed with supportive therapy alone. All four patients positive for HHV6 were treated with systemic corticosteroids (median total dose 6Á5 mg kg À1 , range [2][3][4][5][6][7][8][9][10][11][12][13][14]. Systemic corticosteroids were administered either intravenously or orally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those negative for HHV6, 20 patients were treated with systemic corticosteroids (median total dose 5 mg kg À1 , range 1-16) and five patients were managed with supportive therapy alone. All four patients positive for HHV6 were treated with systemic corticosteroids (median total dose 6Á5 mg kg À1 , range [2][3][4][5][6][7][8][9][10][11][12][13][14]. Systemic corticosteroids were administered either intravenously or orally.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have raised concern that HHV6 positivity in the context of DHS might influence disease severity in affected patients. [6][7][8] In addition, it has been speculated that systemic corticosteroid treatment of those with DHS and concomitant expression of HHV6 may prolong the drug reaction, although it remains unclear whether the presence of HHV6 is pathogenic or only a nonpathogenic marker for disease severity. 5,6,9 Although systemic corticosteroids have been the mainstay of treatment, their efficacy remains controversial.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…HHV-6B reactivation causes encephalitis in immunosuppressed patients. HHV-6B reactivation is also associated with drug-induced hypersensitivity syndrome, and recent studies have suggested that it could be related to the severity of this disease (8,9).…”
mentioning
confidence: 99%
“…Then, transient alteration in immune responses may induce reactivation of viral infections. The latter explains why the clinical findings continue after the patient stops taking the medication 2 3…”
Section: Discussionmentioning
confidence: 99%